Edukasi Kesehatan Tentang Jajanan Sehat di MIN 25 Aceh Besar - Ellyza Fazlylawati; Muhammad Reza Rizki; Nurul Amna; Fajri Fajri; Dela Saimona; Ainal Marziah; Wahyu Febrian (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Background: One way to improve human quality, especially for school-aged children, is by providing nutritious snacks that can meet nutritional needs during learning activities. In Indonesia, many snacks are available in school environments, but many of them are unhealthy when viewed from the color and ingredients used. Community Service Objective: Provide health education about healthy snacks. Method: The method used in this community service activity is lecture and question and answer, to provide an understanding of the importance of choosing healthy snacks for school-aged children. Results: Providing education about healthy snacks increased the understanding of children at MIN 25 Aceh Besar. Children responded well and several students asked questions related to the material about healthy snacks presented. Conclusion: The understanding of MIN 25 Aceh Besar students about healthy snacks increased after participating in the counseling activity. Students showed a higher interest and awareness of the importance of choosing healthy snacks for their health. Keywords; Health Education, Healthy Snacks